Empowering Elderly People for Disinformation Education in the Digital Age - An Activity Linked to University Extension - Lira, Caroline Barbosa de Oliveira; Santos, Suzane Santos dos; Galvão, Vinicius Ferreira; Rodrigues, Kamila Rios da Hora (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
The following paper describes the results regarding an extension course carried out with elderly people in a public university, about fake news and disinformation. The proliferation of misinformation and fake news in digital platforms and media represents a growing societal challenge, especially for the elderly, who may be more susceptible to the spread and manipulation of fake news. In this experience report, we describe the implementation of a course for this audience, which focuses on developing skills to identify and verify online information, combat misinformation, and strengthen the digital autonomy of this demographic. Thirty-four elderly people were present and pointed out positive satisfaction with the course.